Hubungan Konsumsi Beras Merah Terhadap Gula Darah Pada Pasien Diabetes Mellitus Tipe II di Puskesmas Minasa Upa Makassar - Kasmawati Kasmawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
DM is a disease with a fairly high number of sufferers in Indonesia, where based on 2018 RISKESDAS data, there are around 10.3 million people with DM. One effort to improve blood sugar in DM patients is by consuming brown rice which can reduce the risk of developing type II DM. This is because the magnesium content in brown rice aleurone can increase glucose metabolism in the blood by increasing the secretion of the insulin hormone. The purpose of this study was to determine the relationship between brown rice consumption and blood sugar in patients with type II diabetes mellitus at the Minasa Upa Health Center, Makassar. This type of research is analytical research with a cross sectional research design. The results of statistical tests using the chi-square test, there is a relationship between brown rice consumption and blood sugar in patients with type II diabetes mellitus (ρ = 0.000). The conclusion in this study is that there is a relationship between brown rice consumption and blood sugar in type II DM patients. It is recommended that there is awareness to pay more attention to the types of food eaten every day, namely by consuming brown rice as a substitute for white rice.